Design Of Mobile Application Prototype For Surya Mart UM Buton Mini Market - Rasyid Asruddin, Muhammad Abdur; -, Darmawan; Amin, Nasrul (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 6 No 1 (2025): JITTER, Vol.6, No.1, April 2025, 2025)
This study aims to design a mobile application prototype for Surya Mart Universitas Muhammadiyah Buton with a Design Thinking approach, as a solution to operational challenges such as manual transactions, unintegrated inventory management, and limited customer service. The research method follows five stages of Design Thinking, namely: empathize, define, ideate, prototype, and test. Data were collected through observation and interviews with students, lecturers, and staff as potential users. The results of the analysis show the main needs in the form of access to stock information, online ordering, digital payment methods, and promotional notifications. The application prototype was developed using Figma and tested through User Acceptance Testing and Usability Testing. The evaluation showed that the majority of users found the prototype easy to use, the navigation was intuitive, and the features offered were relevant to their needs. Recommendations for improvement include improving navigation icons, payment confirmation, and improving notification features. This study produced a mobile application prototype and scientific publications that are expected to contribute to the optimization of digital-based retail services in the campus environment.